Carbon Tax Guide : A Handbook for Policy Makers - Partnership for Market Readiness (World Bank, Washington, DC, 2017)
Recent years have seen renewed and growing interest in carbon taxes that put a price on greenhouse gas (GHG) emissions. This resurgence in interest has come as over three-quarters of the world have developed Nationally Determined Contributions under the Paris Agreement and are looking for cost-effective ways to achieve these emission reduction goals. It has also developed alongside a gradual shift toward taxes on goods and services, with many jurisdictions seeking to use the tax system to achieve greater economic efficiency and to pursue a range of policy goals beyond raising revenue. Experience has shown carbon taxes to be versatile instruments that are capable of being adapted to a wide range of policy goals and national contexts. This Guide provides a practical tool to help policymakers determine whether a carbon tax is the right instrument to achieve their policy goals and to support them in designing and implementing a tax that is best suited to their specific needs, circumstances and objectives. The guide provides both conceptual analysis and important practical lessons learned from implementing carbon taxes around the world.